Encompassing Learner-Centered Activities through Lesson Study Towards a Constructivist Classroom - et. al., Joanabelle Zita, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to raise conversations on designing appropriate learner-centered activities using the approach of Lesson Study to evaluate classroom practices. Through Lesson Study, the researchers carefully designed the lesson in triangle similarity, considering the principles of constructivism and student-centered learning, and executed the lesson in a class. Two emergent perspectives were apparent: (1) constructivism in mathematics classroom could go beyond discovery learning; and (2) anticipating student responses and capitalizing on possible student misconceptions is a powerful tool in designing constructivist lessons. The study suggests that being a constructivist teacher entails a long journey of classroom experiences and being able to reflect on one’s practice, especially if this is in relation to the students’ learning. Constructivist mathematics classroom activities requires presence of higher-order thinking skills, well-established prior knowledge, and social interaction.